Development and testing of applications created with the platforms Node.js and Laravel - Bomba, Vasyl; Łukasik, Edyta (Journal of Computer Sciences Institute, 2016)
The aim of this work was the analysis and research of software platform Node.js and the framework Laravel, and comparing the performance of the created sites using Node.js and PHP. The tests were carried out with Apache Benchmark and Apache JMeter. The analysis includes theoretical and practical aspects of their functioning.